‘Making known’ or ‘counting our children’? Constructing and caring for children in epidemic South Africa (Medicine Anthropology Theory, 2014)
The article explores how regimes of documentation, quantification, evidence, and accountability have come to shape encounters between program implementers, researchers, young people, and caregivers in one locality in northeastern KwaZulu-Natal, South Africa. Rather than simply critiquing the overemphasis on counting and accounting in global health, I examine the effects of these processes on the provision of services to young people and families. For those whose lives had been systematically excluded from view, processes of form filling could in fact be construed as services in themselves. Further, encounters structured around form filling could work to facilitate other modes of engagement, centered on the construction of forms of recognition, reciprocity, and obligation, and mediated by complex networks of patronage and dependence. Drawing on these findings, the article describes how local histories and contemporary life experiences can shape the ways in which technologies of global health are taken up, and their effects on everyday life.